2017
DOI: 10.1016/j.ajog.2017.05.023
|View full text |Cite
|
Sign up to set email alerts
|

The association of single-nucleotide polymorphisms in the oxytocin receptor and G protein–coupled receptor kinase 6 ( GRK6 ) genes with oxytocin dosing requirements and labor outcomes

Abstract: Background Oxytocin is a potent uterotonic agent that is widely used for induction and augmentation of labor. Oxytocin has a narrow therapeutic index and the optimal dosing for any individual woman varies widely. Objective The objective of this study was to determine if genetic variation in the oxytocin receptor (OXTR) or in the gene encoding G protein-coupled receptor kinase 6 (GRK6), which regulates desensitization of the OXTR, could explain variation in oxytocin dosing and labor outcomes among women being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Some pathogenic dysfunction may also play a role, including such as the synthesis dysfunction of oxytocin and prostaglandins or decreased sensitivity or expression of OXTRs, FP receptors, EP1 receptors, or EP3 receptors. Reinl et al [28] have suggested that some OXTR gene variants are associated with increased oxytocin responsiveness during labor. Grotegut et al [29] reported that the genetic variation in OXTR and gene encoding G protein-coupled receptor kinase-6, which regulates desensitization of the OXTR, is associated with the amount of oxytocin required as well as the duration of labor.…”
Section: Discussionmentioning
confidence: 99%
“…Some pathogenic dysfunction may also play a role, including such as the synthesis dysfunction of oxytocin and prostaglandins or decreased sensitivity or expression of OXTRs, FP receptors, EP1 receptors, or EP3 receptors. Reinl et al [28] have suggested that some OXTR gene variants are associated with increased oxytocin responsiveness during labor. Grotegut et al [29] reported that the genetic variation in OXTR and gene encoding G protein-coupled receptor kinase-6, which regulates desensitization of the OXTR, is associated with the amount of oxytocin required as well as the duration of labor.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed an association between this sequence variant and a lower risk for cesarean section among women induced near term. This lower cesarean section rate was associated with a lower OXT dose, lower maximal OXT infusion rate and lower duration of labor induction with OXT [11]. Increased response of the myometrium to OXT stimulation might explain the observed lower cesarean rate.…”
Section: Discussionmentioning
confidence: 99%
“…Our work, performed with myometrium samples from 60 patients, suggests that patients with rs237888 and/or rs4686302 may be more sensitive to OXT stimulation. This might explain why patients with these variants less often need a cesarean in the course of labor induction with OXT [11] and were thought to be prone to preterm labor [8], respectively]. Additional research should estimate possible clinical benefits of introducing an rs237888 and rs4686302 screening at pregnancy begin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxytocin receptor is considered a Class A GPCR with respect to its interaction with β-arrestins, meaning that it maintains a strong connection with β-arrestin to regulate its endocytosis into secretory or degradative pathways ( Conti et al, 2009 ). The interaction of OXTR with β-arrestins, and therefore its desensitization, is initiated by phosphorylation of the receptor by G protein receptor kinase 6 ( Grotegut et al, 2016 , 2017 ). Studies on OXTR tagged with GFP suggest that many receptors are recycled back though the secretory pathway, indicating a more sustained need for OXTR pathway signaling.…”
Section: The Oxytocin Receptormentioning
confidence: 99%